Thesis production with descriptive hypothesis in top Peruvian universities during the pandemic - Cuba-Vargas, Karen (2024)
Objective: To analyze the prevalence of the use of descriptive hypotheses in theses presented at top universities in Peru during 2020. Methods: A quantitative, descriptive, and cross-sectional study was conducted. The population included theses available in the digital repositories of leading Peruvian universities. The sample was intentionally selected, considering undergraduate and graduate theses from various faculties. Data were obtained through document review and categorization of theses based on the type of hypothesis used. Descriptive statistics were employed to determine frequencies and percentages, and comparisons were made between academic levels. Results: It was found that 45 % of the analyzed theses employed descriptive hypotheses, which were more common at the undergraduate level (55 %) compared to the graduate level (35 %). Additionally, a higher recurrence of descriptive hypotheses was observed in the Social Sciences and Education faculties. Conclusions: Thesis production in top Peruvian universities during the pandemic shows a significant use of descriptive hypotheses, particularly at the undergraduate level and in certain faculties, which may be related to the nature of study programs and the methodological training provided.